HE I 5876 LINE STRUCTURE IN THE SPECTRA OF IL CEP A - Ismailov, N. Z.; Khalilov, O. V.; Bahaddinova, G. R. (Одеські астрономічні публікації, 2016)
We are presents the results of researches of the He l λ5876 Å (D3) line in the spectrum of Herbig Be type star IL Cep A. This line represents the absorption structure which has a width on the level of the continuum about 15-18 Å, and a FWHM about 6-8 Å. It is shown that the line Hel λ5876 Å has a complex, multicomponent structure. The average value of the radial velocities showed smooth variability, and the maximum value Vr achieved in 2009-2010. Large scatter in radial velocity was obtained in 2013 and 2014. The equivalent width of the line also shows significant changes from year to year, and during the observation season. The total average value of this parameter remains constant for all observations. For all of the data, a mean value of the equivalent width of the absorption is equal 0.56±0.025 Å, and the standard deviation ±0.16 Å from the mean. The observed features in the line indicates that the field of origin this line has a complex structure and physical conditions.